Simulation analysis on network layer attacks in wireless mesh networks - Ganesh Reddy, K; S. Sudheer, M; Kiran Sree, P; Purushothama Raju, V (International Journal of Engineering and Technology, 2018)
Security mechanisms in Wireless Mesh Networks (WMNs) play an essential role to protect WMNs features. However, the existing security standards of WMNs are still in draft state. In addition to that, WMNs features like integrating with heterogeneous nodes and networks, which make designing robust security mechanism for WMNs is more complex. To develop an efficient security mechanism for WMNs, firstly we need to study the vulnerabilities of WMNs, and then exploit these vulnerabilities to perform various attacks and find the counter measures for these attacks. In this paper, we have studied various network layer attacks, based on this study we identified the interdependencies of these attacks. We use AODV protocol to exploit these attacks. Our simulation results show that the each attack severity with respect to goodput and Packet Delivery Ratio (PDR). We explained how these severity measures are useful for future WMNs security mechanisms.Â
Keywords: Use about five key words or phrases in alphabetical order; Separated by Semicolon.